Analysis of the body mechanism of Taijiquan health promotion - Ren, Tianping; Li, Wugong; Chang, Zhaoyang (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: The Outline of the Healthy China 2030 Plan and the Plan for the Development of Traditional Chinese Medicine Health Services (2015-2020) both clearly point out that Tai Chi should be used to promote the health of the whole nation. In accordance with the needs of the age for the integration of body and medicine, the purposes of this paper are as follows: 1. Researching on the body mechanism of quiet nurturing of Taijiquan pile exercise to improve health; 2. Researching on the mechanism of moving nurturing of Taijiquan frame to improve health. Metherds: sorting out the basic ideas and methods of Taijiquan to improve health in Taijiquan books and articles with method of literature; with the method of oral history, sorting out the experiences of Taijiquan practicers, collecting first-hand data to prove the remarkable effects of Taijiquan to improve health. Results: 1)Taijiquan has a strong gene to promote human health: A healthy life without a long life is a regrettable one. Similarly, only a long life without a healthy body is a painful life. People want to live a long and healthy life. If the body’s internal organs function (internal cause) always maintain a healthy state, there will be no more suffering from disease and mental pain. Taijiquan is from the internal body practice to achieve the role of health. Taijiquan is the study of physical and mental cultivation. It is a part of human life science, the precious heritage of Chinese traditional culture, the crystallization of national wisdom and an important content of Chinese culture and Chinese elements. It has the effect of expelling disease and prolonging life, self-defense and self-cultivation, as well as profound cultural connotation, and has become a necessary fitness method and health keeping method in human life. “The sky has three treasures: the sun, the moon and the stars; The earth has the three treasures: water, fire and wind; man has the three treasures: essence, qi and spirit. ” A man’s health is determined by his strength of mind. Three jewels do not harm health, sickness, exhaustion and fear of death. Essence is an important element to maintain the normal state of human body and extend life. Qi is the most basic material that constitutes human life activity. Spirit is born of qi, which is full of spirit. Essence is the core of traditional health maintenance. From the perspective of health, essence nourishes the spirit of the root gas and qi nourishes spirit. Essence is the source of life. The way to keep healthy is to take essence as treasure. Essence can be angry, gas can give birth to god, good health of the people to raise its essence. If the qi is full, the spirit is full; if the spirit is full, the body is healthy; if the spirit is poor, the qi is poor. 2)Taijiquan pile exercise is the best way to rest: Taijiquan piles include round piles, gas extraction piles, false and solid piles, etc. Pile work should be coordinated with breathing from the beginning to the end, meaning Dantian, and taking Dantian movement as the core of cultivation. Through refining refined qi, refining the process of gasification of spirit, to achieve the concentration of the three treasures of spirit. Why does Taijiquan pile function to condense the three treasures? The principle is to stimulate the body meridian compatible meridian acupoints of many health functions. The station pile firstly mobilizes the two legs "Zusanli", a pair of big points, and feels the overhead wire hanging (Taijiquan is called "virtual jaw jacking movement"), and mobilizes the "Baihui" points on the top of the head. The two arms around mobilizes the Laogong point of both hands, and the standing state of the sole of the foot mobilizes the Yongquan point of both feet. The heart lives in fire, the kidney in water. Mobilize the two laogong points, two yongquan points, the two pairs of points, to achieve the fire and water, let the heart and kidney together, that is, the station pile will make the two hands, two feet center fever. Taijiquan pile work also requires that the body is upright, with chest collapse, the whole body is relaxed, and the two veins of the governor are mobilized. So the Yin and Yang collaterals of the whole body, all mobilized. Traditional Chinese medicine says “If the body is unobstructed, there will be no pain". Taijiquan requires the tongue to touch the palate, so that the two veins of the governor can be connected, the heaven and earth intersect, Yin and Yang mingle, and the spirit of jade fluid (i. e. , saliva, holy water or dragon salivation) can be constantly poured out. This is very important for refining qi. 3) Tai Chi exercise frame is the best way for moving nurture: Taijiquan frame is the best form of moving and nourishing the three treasures, because it is the best aerobic metabolic exercise. Tai Chi action is slow and soft, deep breath deep inhalation, breathing long and thin, in the exhalation, the life door back to support the abdomen before and after the expansion, the diaphragm rise so that the abdomen spit out more qi with turbidity with the carbon dioxide out of the body. When inhaling, the chest expands so as to increase the vital capacity. When inhaling, the vital gate naturally recovers, the lower abdomen contracts before and after, the diaphragm sinks, and inhales more fresh oxygen. This is an aerobic exercise. Taijiquan requires that the mind guide the qi, the body move with the qi, the body move without any movement, and the internal Qigong leads to the external movement. Taijiquan is “round in silence and twisted in motion”. All movements are spirally wound, either straight or reverse. In this way, the meridians and collaterals are unblocked and the oxygen and blood flow in the viscera are unblocked. Taijiquan is a kind of advanced kung fu which combines both internal and external practice, combines mind, qi and strength, and combines essence, qi and spirit, integrating fitness, protecting the body, improving the brain, refreshing, prolonging life and nourishing the nature. The internal functions of Taijiquan are mainly Qigong. Zhou Tiangong is an important part of Qigong and also an important part of the meridian theory of Chinese medicine. The inner rotation of the red field refines the essence, the opening and closing of the heavens refines the spirit, and the mental adjustment refines the spirit. The essence exists in the inside, the qi travels in the body, the magic passes in oneself, the appearance is special arc, the internal strength is special spiral. In particular, the combination of Dantian inner turning and Qi sinking Dantian is the best way to refine Qi, purify the spirit and invigorate the mind. Conclusion: No matter it is the "sanbao" of tai chi piling skill or the "sanbao" of tai chi moving skill (routine), only the correct posture, one move and one form, in line with the requirements of tai chi theory, can we practice tai chi really well. Taijiquan practicing can realize the purpose of keeping healthy, the reflections are as follows: 1. Collecting the spirit, air and soul to realizing the purpose of refining the spirit and guiding the air to go around the body with “quiet nurturing” of pile exercise to get through the acupoints; 2. Fully motivating the function of eternal and outside organs to realize the purpose of health through “moving nurture” of Taijiquan practice.